2007
DOI: 10.1002/uog.4104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of endometrial morphology and vascularity to predict endometrial malignancy in women with postmenopausal bleeding and sonographic endometrial thickness ≥ 4.5 mm

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 19 publications
7
90
2
4
Order By: Relevance
“…The interobserver agreement between two experienced examiners was excellent for ET measurement in our own study with a Kappa value of 0.8 30 . Opolskiene and co‐workers found that the inter‐observer agreement between two experienced examiner for endometrial morphology assessment was generally moderate to good, with a kappa value of 0.49–0.78 21 . Assessment of vascular morphology showed a similar reproducibility as previously reported for endometrial thickness measurements 21 , 30 .…”
Section: Novel Techniques For Risk‐estimation Of Endometrial Malignansupporting
confidence: 85%
See 3 more Smart Citations
“…The interobserver agreement between two experienced examiners was excellent for ET measurement in our own study with a Kappa value of 0.8 30 . Opolskiene and co‐workers found that the inter‐observer agreement between two experienced examiner for endometrial morphology assessment was generally moderate to good, with a kappa value of 0.49–0.78 21 . Assessment of vascular morphology showed a similar reproducibility as previously reported for endometrial thickness measurements 21 , 30 .…”
Section: Novel Techniques For Risk‐estimation Of Endometrial Malignansupporting
confidence: 85%
“…There are, however, several studies showing that endometrial morphology assessment can be useful in the prediction of endometrial cancer 20 23 . Endometrial echogenicity and border in combination with ET has been shown to be a better predictor of endometrial cancer than ET measurement alone 21 23 . The best predictor of cancer at SIS is the finding of an irregular surface focal lesion (sensitivity 89% specificity 67%), Fig.…”
Section: Novel Techniques For Risk‐estimation Of Endometrial Malignanmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many women with postmenopausal bleeding and endometrial thickness ≥ 5 mm do not have endometrial cancer and some do not have any endometrial pathology at all, but will still undergo -perhaps unnecessarily -interventional diagnostic procedures such as dilatation and curettage (D&C) or hysteroscopy. In the high-risk group of women with postmenopausal bleeding and a thick endometrium, the thicker the endometrium the higher the risk of malignancy 3,4 . Diagnostic methods other than a simple measurement of endometrial thickness, e.g.…”
Section: Introductionmentioning
confidence: 99%